2021
DOI: 10.3390/ijerph182111088
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Association between Asbestos Exposure and Esophageal Cancer

Abstract: Background: We conducted a meta-analysis to quantitatively assess the association between asbestos exposure and esophageal cancer. Methods: We systematically collected articles from three electronic databases and calculated the pooled standardized mortality rate (SMR) from the meta-analysis. Subgroup analysis according to the type of asbestos exposure, follow-up years, sample size, industry classification, sex, and high-dose exposure was conducted. Results: From 242 studies, 34 cohort studies were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Our study consistent with two previous studies (Institute of Medicine; Wu et al) 16,17 suggested an association between occupational asbestos exposure and EC risk by considering some specific job categories and these results were relevant to both histological types of EC. Thus, by adding EC among the possible targets of asbestos carcinogenicity, our results could lead to recommendations for reducing occupational asbestos exposure and implementing strict guidelines regarding occupational asbestos exposure.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study consistent with two previous studies (Institute of Medicine; Wu et al) 16,17 suggested an association between occupational asbestos exposure and EC risk by considering some specific job categories and these results were relevant to both histological types of EC. Thus, by adding EC among the possible targets of asbestos carcinogenicity, our results could lead to recommendations for reducing occupational asbestos exposure and implementing strict guidelines regarding occupational asbestos exposure.…”
Section: Discussionsupporting
confidence: 93%
“…7,13 Some studies also showed an association between asbestos exposure particularly from drinking water and digestive system cancers, such as colon cancer. 10,14,15 Wu et al 16 reported that occupational or environmental asbestos exposure might increase the risk of EC by focusing on 34 cohort studies and also the Institute of Medicine (US) Committee on Asbestos in 2006 reported a meta-analysis according to the three case control and 19 cohort studies 17 both reviews, however, did not appear to include all available studies, and some concerns remain regarding the different types of studies, types of histology, and geographical areas, thus justifying an updated review.…”
Section: Introductionmentioning
confidence: 99%
“…6 ) for which gallstones have been implicated 31 33 , and the other is the mesothelioma-esophageal cancer pair (Fig. 7 ) for which exposure to asbestos has been implicated 34 , 35 . It can be seen that the immunogenetic HLA profiles of all these 6 cancer pairs were positively and highly significantly associated ( P < 0.001 for all correlations), attesting to the congruence of existing data from other studies.…”
Section: Resultsmentioning
confidence: 99%
“…A majority of pleural mesothelioma cases are due to asbestos 9 . The association of asbestos exposure and other malignancies has been studied with variable results, as authors of recent reviews and meta-analyses have claimed that asbestos is a risk factor for esophageal and colorectal cancers, whereas no association was found with kidney and prostate cancers 10–13 …”
mentioning
confidence: 99%
“…9 The association of asbestos exposure and other malignancies has been studied with variable results, as authors of recent reviews and meta-analyses have claimed that asbestos is a risk factor for esophageal and colorectal cancers, whereas no association was found with kidney and prostate cancers. [10][11][12][13] Given that little is known about the nonmalignant comorbidities of asbestosis patients, our aim was to investigate the comorbidities as well as both the underlying and immediate causes of death of patients with asbestosis. Furthermore, the association of the most common comorbidities with the prognosis of asbestosis patients was evaluated.…”
mentioning
confidence: 99%